(untitled) (Research, Society and Development, 2020)
The objective of the work was to characterize the morphophysiological parameters of rubber tree rootstocks from seeds of clones GT1, PB235 and IAN873, grown in a suspended nursery in the municipality of Ilha Solteira-SP. The experiment was carried out in an open-air nursery installed at the Faculty of Engineering - UNESP, Campus de Ilha Solteira - SP, from March / 2018 to January / 2019. The experimental design used was randomized blocks, in a 3 x 5 factorial scheme, with three rootstocks GT1, PB235 and IAN873 and five times of data collection 60, 120, 180, 240 and 300 days after transplantation (DAT ), with three repetitions of 10 seedlings per plot. The rootstocks showed significant variation in physiological and growth parameters over the experimental period. IAN873 stood out in the increase of stem diameter, Dickson’s quality index and relative chlorophyll content, as indicated by the reading of the SPAD-502 index. The photosynthetic rate of IAN873 was low at the beginning of the evaluations (60 DAT), however, it increased linearly, being equal to the other clones at the end of 300 DAT. During the cultivation period (300 DAT), under suspended nursery conditions, the IAN873 genotype demonstrated greater aptitude for use as a rootstock.